Subsidiary evolution in a transition economy: Kemira GrowHow in the Russian fertilizer market - Viktorija V. Golikova; Päivi Karhunen; Riitta Kosonen (Journal for East European Management Studies, 2011)
This paper illustrates subsidiary evolution in a transition economy through the development of a multinational company's Russian subsidiary. Building on the concept of subsidiary evolution, we analyze how knowledge transfer from headquarters and application of the subsidiary management's local knowledge contributed to the process of change. Our empirical analysis is based on four in-depth interviews with senior managers from the company's headquarters and the Russian subsidiary and on documentary evidence. Our results show that the subsidiary capabilities were developed as a combination of knowledge transfer from headquarters at the beginning of the operations and of learning by the Russian management. – – Der Artikel illustriert die Entwicklung einer Tochtergesellschaft in einer Transformationswirtschaft am Beispiel der russischen Niederlassung eines multinationalen Konzerns. Aufbauend auf dem Konzept der Filialentwicklung analysieren wir, wie der Wissentransfer von der Muttergesellschaft und die Anwendung der Kenntnisse des lokalen Managements zum Wandlungsprozess beigetragen haben. Unsere empirische Analyse basiert auf vier Tiefeninterviews mit Bereichsleitern aus der Muttergesellschaft und der russischen Tochter sowie auf einer Dokumentenanalyse. Unsere Ergebnisse zeigen, dass die Leistungsfähigkeit der Tochtergesellschaft ausgebaut wurde sowohl durch Wissenstransfer von der Muttergesellschaft zu Beginn des Operationen als auch durch einen Lernprozess auf Seiten des russischen Managements.
Keywords: 650; subsidiary evolution; knowledge; foreign entry; Russia